WASTE REDUCTION IN CARMINIC ACID PRODUCTION BY APPLYING PINCH TECHNOLOGY - Erazo E., Raymundo (2005)
An integrated approach to the design and analisis of heat exchanger networrks (HEN) Is outlined. A case study is used, carminic acid,, to illustrate this integrated approach, to emphasize the economy of 60% energy with respect to convectional process.